2005
DOI: 10.1128/jcm.43.12.5916-5924.2005
|View full text |Cite
|
Sign up to set email alerts
|

Use of Recombinant Antigens for Early Postnatal Diagnosis of Congenital Toxoplasmosis

Abstract: The main objective of this work was to improve the early serologic diagnosis of toxoplasmosis in children at risk of congenital infection by using recombinant antigens. Serum samples from 104 infants born to mothers with primary Toxoplasma gondii infection acquired during pregnancy, of which 35 were congenitally infected and 22 had clinical silent toxoplasmosis at birth, were included. Immunoglobulin M (IgM), IgG, and IgG subtype antibodies against epitopes carried by fragments of T. gondii MIC2, MIC3, MIC4, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 44 publications
4
30
0
1
Order By: Relevance
“…Several other recombinant antigens give similar results, but they were not included in the commercial assays. As the results were similar but weaker than for whole extract ELISA, attempts have been made to introduce a mixture of several recombinant antigens or chimeric proteins composed of several epitopes of diverse T. gondii proteins (BUFFOLANO et al, 2005;BEGHETTO et al, 2006;PIETKIEWICZ et al, 2007). However, all attempts have given similar results without improving upon the results of the whole extract ELISA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other recombinant antigens give similar results, but they were not included in the commercial assays. As the results were similar but weaker than for whole extract ELISA, attempts have been made to introduce a mixture of several recombinant antigens or chimeric proteins composed of several epitopes of diverse T. gondii proteins (BUFFOLANO et al, 2005;BEGHETTO et al, 2006;PIETKIEWICZ et al, 2007). However, all attempts have given similar results without improving upon the results of the whole extract ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…There are several strains of T. gondii with variable virulence and some antigenic differences, despite the fact that all are reactive to whole extract antigens (KONG et al, 2003). These minor antigenic differences could affect ELISA with few epitopes, as observed in most isolated recombinant protein ELISA, which usually present less sensitivity and specificity than whole extract ELISA (BUFFOLANO et al, 2005). Another aspect is the parasite load in human infection, which can be acquired by oocyst ingestion of only eight sporozoites, or by tissue cysts in raw meat, containing several cysts with thousands of bradyzoites, as reported in experimental models comparing these two ways of infection and reporting that cyst induced infection was more acute and severe than oocyst induced infection (DUBEY, 2006).…”
mentioning
confidence: 99%
“…Under these proteins, classic secretory antigens like macrophage-inhibitory cytokine 2 (MIC2), MIC5 (H4), GRA1, and GRA7 were observed. Judging as a proof of principle, these proteins have already been previously described as diagnostic markers (4,16,24). Besides, a protein with a molecular mass of about 80 kDa and a pI of 5 reacted also with Toxoplasma-specific IgA antibodies of patients with an acute infection.…”
Section: Identification Of Sub1 By 2-de and Mass Spectrometry Analysismentioning
confidence: 99%
“…Moreover, in 30% to 60% of infants with congenital toxoplasmosis, the Toxoplasma-specific IgM antibody response is absent or undetectable by standard serological assays (7,8,10,13). Therefore, the availability of innovative diagnostic methods would be desirable.During the last 10 years, several studies have reported on the use of recombinant antigens for the serological diagnosis of T. gondii infection (1,4,8,17,21,22,27,31). Nevertheless, although they are promising, none of the assays based on recombinant antigens displayed all the characteristics required to replace the tachyzoite antigen in IgG-and IgM-based tests, indicating that further work is needed before an immunoassay with recombinant products will be available for clinical purposes.…”
mentioning
confidence: 99%
“…However, the assays currently available for the detection of specific anti-Toxoplasma antibodies may vary in their abilities to detect serum immunoglobulins (18,23,24,34), due to the lack of a purified standardized Toxoplasma antigen or standard methods for preparation of the antigen. Moreover, in 30% to 60% of infants with congenital toxoplasmosis, the Toxoplasma-specific IgM antibody response is absent or undetectable by standard serological assays (7,8,10,13). Therefore, the availability of innovative diagnostic methods would be desirable.…”
mentioning
confidence: 99%